SME Competitiveness Outlook 2023 - International Trade Centre (United Nations, 2023)
This SME Competitiveness Outlook assesses the impact of conflict and fragility on business performance. It unveils a Fragility Exposure Index, and shows that fragility, as experienced by firms, can be reduced by 25% if they take actions to reinforce competitiveness. These include engaging with business support organizations, improving financial management and retaining skilled staff. The report finds that direct support to firms is helpful and must be complemented by reforms to promote peace and stability and improve the business environment. Humanitarian partners, development agencies and capable state institutions must collaborate, coordinate and have a deep understating of the context to avoid reinforcing the drivers of fragility, and maximize positive outcomes.